Ceramic based 3D integration technology of integrated navigation microsystem - Shen Shijun; He Yilei; Wang Jinhua; Zhuang Yonghe (Dianzi Jishu Yingyong, 2025)
In order to solve the problem of large volume and weight of high-precision integrated navigation system, a new 3D micro system packaging structure is proposed based on System in Package(SiP) technology such as multi-layer ceramic substrate, high-density wiring and 3D assembly. Using SIP processes such as Low Temperature Cofired Ceramic(LTCC) substrate high-density wiring and mounting, substrate stacking and high orthogonal assembly, the triaxial accelerometer, triaxial gyroscope, satellite navigation, geomagnetic meter and barometric altimeter are integrated into one packaging unit. The overall size of the integrated navigation microsystem product is only 3.1 cm×2.9 cm×0.96 cm, and the weighing is only 18 grams, and greatly expanded the application field. Through data fusion algorithms, navigation accuracy and reliability can be effectively improved, presenting broad application prospects.